Factors Associated With Neonatal Intensive Care Follow-up Appointment Compliance. (May 2013) - Harmon, Sara L.; Conaway, Mark; Sinkin, Robert A.; Blackman, James A.
Background and methods . Our goal was to identify factors that affect neonatal intensive care unit (NICU) follow-up appointment compliance. Compliant and noncompliant infants discharged from the NICU over 1 year and scheduled for follow-up (133) were compared retrospectively; a prospective telephone survey of noncompliant families was also undertaken. Results . Maternal drug use (odds ratio [OR] = 0.049, 95% confidence interval [CI] = 0.005-0.506), multiple gestation pregnancy (OR = 0.163, 95% CI = 0.050-0.533), male sex (OR = 0.308, 95% CI = 0.112-0.850), and greater distance from the hospital (OR = 0.987, 95% CI = 0.976-0.999) were independently associated with lower appointment compliance. A greater number of days on oxygen was associated with greater odds of compliance (OR = 1.057, 95% CI = 0.976-0.999). Shorter NICU stays ( P = .047) and less chronic lung disease ( P = .026) were significantly associated with noncompliance by bivariate analysis only. Distance from the hospital and travel expense were the most often self-cited reasons for appointment noncompliance. Conclusion . Understanding factors associated with NICU follow-up noncompliance is a starting point for providing targeted intervention.